Whodonit? Rai Tv Fiction Production Between Detection and Giallo (Cinéma & Cie. Film and Media Studies Journal, 2012)
Italian TV serial production is interesting not only in its peculiar, often paradoxical, production traits, but also because of its adventurously happy results, sometimes due to creative constraints by claustrophobic Italian television market. TV series have a physiognomy and an “Italianness” also evident in their language, since they show distinctive characteristics in terms of modes of representation and communicative pacts, in which to settle a whole television history and visual culture. This essay begins to outline this aspect from a particular vantage point: that of detective and crime series, whose history is deeply rooted in Italian culture and whose dominant traits are so different from most recent European TV series. Far from being a sign of recession, RAI public service broadcasting – in which Il commissario Montalbano naturally represents a relevant case – reveals the persistence of specific and well embedded traits, albeit evolved over time (a particular dynamic between opening and closure; an overwhelming and static narrative; a parataxis and accumulation of criminal performances, which closes continuously narrative development around the circle of the crime; a urban and landscape component which provokes and creates diversions, etc.). The traits are rooted and shaped in Italian culture, starting from the privileged relationship never exhausted with its literary matrix, but also from the complex and typically Italian interconnection in cultural and media domains created by giallo.